Raymond Williams and the radical project of cultural studies - San Juan, Epifanio
"By enlanrging the general interpretation of "culture," Raymond Williams pioneered the formation of a new discipline called "cultural studies" which deployed the categories of class, gender, sexuality, place, and ethnicity in a dialectical analysis of experience of collectives in concrete circumstances. Williams rigorously applied the principle of "historical specificity" derived from classical Marxism, refined and enriched with the ideas of Bakhtin/Voloshinov on language and Gramsi on hegemony, to produce a mode of critique called "militant particularism." His theory of culture and cultural change situated in the context of the intellectual tradition ha is responding to its summarized in this paper."
Keywords: Culture; Cultural studies